2008
DOI: 10.1271/bbb.80252
|View full text |Cite
|
Sign up to set email alerts
|

Absorption, Migration and Kinetics in Peripheral Blood of Orally Administered Ovalbumin in a Mouse Model

Abstract: Intestinal absorption of food proteins is well known, whereas its physiological significance remains to be investigated. Various amounts (1, 10 and 50 mg) of ovalbumin were orally administered to mice and the blood kinetics were subsequently analyzed by two-site ELISA. The blood ovalbumin concentration consistently reached its maximum (7-90 ng/ml) about 20 min after the oral administration and then gradually decreased in a dose-dependent manner. Only intact (45 kDa) and truncated (40 kDa) ovalbumins were alway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…13,26) However, a collective contribution to the LF uptake by some other mechanisms could not be ruled out, because a certain level of uptake by the enterocytes was also apparent for some proteins other than LF in the present and previous studies. 21,22,27) About 60 ng of LF per well of the Caco-2 cells was taken up by the 3-h loading, while about 120 ng (after subtracting the value of 80 ng for the 1-min incubation) of LF was subsequently released into the culture medium during the 3-h culture. Although the reason for these apparently contradictory results between the LF uptake and subsequent release remains unknown at this moment, the association of LF with its receptor, as speculated by the immunocytological analysis (see Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,26) However, a collective contribution to the LF uptake by some other mechanisms could not be ruled out, because a certain level of uptake by the enterocytes was also apparent for some proteins other than LF in the present and previous studies. 21,22,27) About 60 ng of LF per well of the Caco-2 cells was taken up by the 3-h loading, while about 120 ng (after subtracting the value of 80 ng for the 1-min incubation) of LF was subsequently released into the culture medium during the 3-h culture. Although the reason for these apparently contradictory results between the LF uptake and subsequent release remains unknown at this moment, the association of LF with its receptor, as speculated by the immunocytological analysis (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Tel: +81-52-789-4129; Fax: +81-52-789-4128; E-mail: tmatsuda@agr.nagoya-u.ac.jp Abbreviations: DMEM, Dulbecco's modified Eagle's medium; FBS, fetal bovine serum; IntL, intelectin-1; LF, lactoferrin; LY, lysozyme; OA, ovalbumin; OM, ovomucoid; PBS, phosphate-buffered saline; POD, peroxidase ovalbumin (OA), which was taken up from the intestinal lumen, migrated to peripheral blood at a ng/mL level in adult mice 21) and that OA was taken up by the Caco-2 monolayers, degraded within the cells, and partly released in an intact form. 22) In contrast, LF was almost undetectable in the peripheral blood of rats to which LF had been intragastrically administered, 16) and the subcellular localization and dynamics of LF taken up by intestinal epithelial cells have not been well investigated.…”
mentioning
confidence: 99%
“…Some food proteins have been reported to remain intact, at least at immunologically detectable levels, in the lumen of the mouse small intestine. 21,28) It would be of interest to investigate the digestibility or resistance of bovine colostrum IgG in vitro and in vivo using animal models.…”
Section: Discussionmentioning
confidence: 99%
“…IgG antibodies specific for NoV and SaV VLPs in bovine colostrums were measured by ELISA, as described previously. 21) Briefly, 96-well plates (Nunc, Roskilde) were coated with 1 mg per well of VLPs in PBS. After washing and blocking, the plates were incubated with colostrums diluted to a 1-20 mg protein concentration with PBS/ Tween/BSA, washed with PBS/Tween, and incubated with PODconjugated anti-bovine IgG (H and L chains) antibody (Abcam, Cambridge).…”
Section: )mentioning
confidence: 99%
“…However, in most cases, foods are cooked and processed with other foods and undergo significant changes in such qualities as digestibility, absorbability and allergenicity. Some studies of the intestinal absorption of food protein have shown that the concentration of protein in the blood increases in a dose-dependent manner and that co-administration with other food components such as protein or corn oil markedly affects the intestinal absorption of allergen (11,12). Furthermore, allergenicity is altered by denaturation and modification (13)(14)(15), such as that occurring through processing or cooking.…”
Section: Resultsmentioning
confidence: 99%